2017
DOI: 10.1017/brimp.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

The Bangor Gambling Task: Characterising the Performance of Survivors of Traumatic Brain Injury

Abstract: The Bangor Gambling Task (BGT, Bowman & Turnbull, 2004) is a simple test of emotion-based decision making, with contingencies varying across five blocks of 20 trials. This is the first study to characterise BGT performance in survivors of traumatic brain injury (TBI) relative to healthy controls. The study also aimed to explore sub-groups (cluster analysis), and identify predictors of task performance (multiple regression). Thirty survivors of TBI and thirty-nine controls completed the BGT and measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Similarly, a recent case-control study by Bhatti et al [28] found that prior TBI was a significant predictor of subsequent gambling problems, particularly among middle-aged men, those who reported alcohol or tobacco use, and those who experienced multiple TBIs. The link between TBI and gambling is also supported by recent neurological research [29] and animal research [30].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, a recent case-control study by Bhatti et al [28] found that prior TBI was a significant predictor of subsequent gambling problems, particularly among middle-aged men, those who reported alcohol or tobacco use, and those who experienced multiple TBIs. The link between TBI and gambling is also supported by recent neurological research [29] and animal research [30].…”
Section: Introductionmentioning
confidence: 82%
“…Traumatic Brain Injury (TBI) is caused by a blow to the head by an external force, or sudden movement, that can lead to serious long-term consequences [18][19][20]. TBI is a common form of injury that can result in changes in behavior, emotion and/or cognitive function [27][28][29]. Individuals reporting past TBI are also more likely to report substance misuse, aggressive behaviors, and mental health and substance use problems [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other facets of social cognition such as the development of social knowledge and morality are particularly relevant to children in whom maturational processes are complicated by the presence of brain injury, as discussed in this volume (Chiasson, Elkaim, Well, Crevier, & Beauchamp, 2017). Social cognition also impinges on behaviour such as the capacity to make effective decisions to enhance prosocial engagement (Adlam, Adams, Turnbull, Yeates, & Gracey, 2017) while inhibiting antisocial urges (Honan, Allen, Fisher, Osborne-Crowley, & McDonald, 2017).…”
Section: Defining the Sub-components Of Social Cognitionmentioning
confidence: 99%
“…Given that the BGT is simpler to administer than the IGT, it constitutes a promising tool to assess patients with possible prefrontal dysfunction in clinical settings more quicker and easier (Adlam et al, 2017(Adlam et al, , 2009). In addition, the replaceable alternative to measure the same construct opens up new possibilities to investigate changes over time.…”
Section: Introductionmentioning
confidence: 99%